A new robust delayless subband adaptive filtering algorithm with variable step sizes for active control of broadband noise. (May 2021) - Long, Guo; Lim, Teik C.
Abstract: Conventional delayless subband active noise control (ANC) systems can be degraded by the unexpected impulsive disturbances in the reference signal and/or the residual error signals despite the fact that the step sizes have been normalized by the variances of subband signals. Another inherent drawback is that an undesirable delay is introduced into the weight update path by using analysis filter banks, which reduces the upper bound of the step sizes thus limits the convergence rate. This paper proposes a novel robust and effective ANC algorithm configured in the delayless subband architecture for broadband noise cancellation. Instead of real-time providing threshold(s) on the reference and/or error signal as applied in most of the existing ANC algorithms for robustness, an online tuning scheme of bounded step sizes for the adaptive learning is developed for better convergence and outlier suppression. Box-constraint and time-averaging scheme deployed in the step size tuning guarantee robustness without requiring very accurate a priori information of the noises which might be corrupted by the impulses in real-world applications. In particular, this paper presents the stability and convergence analysis of the proposed closed-loop ANC system. Moreover, the computational complexity advantage is justified when compared to other state-of-the-art robust ANC algorithms. Numerical simulations are performed to validate the enhanced performance of the proposed algorithm for various colored noises with or without impulsive interferences.